Videomicroscopy as a tool for investigation of the microcirculation in the newborn. Issue 19 (30th September 2016) - Wright, Ian M. R.; Latter, Joanna L.; Dyson, Rebecca M.; Levi, Chris R.; Clifton, Vicki L.
Abstract: The perinatal period remains a time of significant risk of death or disability. Increasing evidence suggests that this depends on microcirculatory behavior. Sidestream dark‐field orthogonal polarized light videomicroscopy (OPS) has emerged as a useful assessment of adult microcirculation but the values derived are not delineated for the newborn. We aimed to define these parameters in well term newborn infants. Demographic details were collected prospectively on 42 healthy term neonates ( n = 20 females, n = 22 males). OPS videomicroscopy (Microscan) was used to view ear conch skin microcirculation at 6, 24, and 72 h of age. Stored video was analyzed by a masked observer using proprietary software. There were no significant differences between the sexes for any structural parameters at any time point. There was a significant increase over time in small vessel perfusion in female infants only ( P = 0.009). A number of 6‐ and 72‐h measurements were significantly correlated, but differed from the 24‐h values. These observations confirm the utility of the ear conch for neonatal microvascular videomicroscopy. They provide a baseline for studies into the use of OPS videomicroscopy in infants. The changes observed are comparable with previous studies of term infants using these and other microvascular techniques. It is recommended that studies for examining the mature neonatal microvascular structure be delayed until 72 h of life, but studies of the physiology of cardiovascular transition should include the 24‐h time point after delivery. Abstract : This paper delineates the normal values obtained for a whole series of videomicroscopic structural and functional parameters in the newborn over the first 3 days of life. This lays the groundwork for future videomicroscopic assessment of the cutaneous microcirculation in the sicker and more premature infant, as well as for future studies of programmed changes in microcirculatory physiology.